A utilização da gamificação para engajamento de equipes: um estudo de caso sobre a aplicação de um jogo empresarial em uma instituição financeira - Santinho, Cristiane Catarino (2018)
Gamification has been gaining strength within organizations as a way of engaging and influencing behaviors of its employees to achieve better results. Although the use of games is old and can be applied to several fields of knowledge, gamification within the corporate environment has only grown in recent decades, arousing interest in companies as a way to increase the engagement of their employees. The purpose of this paper was to raise and explore the main effects of gamification within the corporate environment and to understand how it contributes to generate engagement. Through a case study within a financial institution that recently introduced gamification as a management tool, it was sought to identify the resulting impacts with its application, listing the main perceptions of managers and participants, as well as their positive aspects, challenges, and necessary improvements. Together, allied concepts and requirements raised in the literature review to the case studied, confronting the practice with theory. With this, it was verified that the gamification is an effective instrument of management, being a strategy well seen by the employees. However, attention must be paid to the suitability of some elements and characteristics of gamification, which are determinants for its success, whether: player profiles, relevance of the functionalities, form of communication of the rules and functioning of the dynamics of the game, and attractiveness of rewards. If these factors are not treated properly and consistently, there will be a lack of interest in the tool, undermining its positive effects.